A study on the population dynamics of Labeo rohita (Hamilton) in the Sylhet basin, Bangladesh - Amin, S M Nurul; Haroon, A K Yousuf; Alam, M (Indian Journal of Fisheries, 2011)
Data collected on the population parameters of Labeo rohita (Hamilton) from theSylhet basin, north-eastern part of Bangladesh were analysed using lengthfrequencybased FiSAT software. The von Bertalanffy growth parameters LÂ°Â° andK for the species were 80.20 cm and 0.41/year respectively. The annual rate ofnatural (M), fishing (F) and total mortality (Z) were found to be 0.73, 0.83 and1.56 respectively. The estimated rate of exploitation (E) is 0.52. Recruitment ofthis species into the fishery takes place during April - June and October - Novemberwith peaks during May and October. Emix was found to be 0.4452. The relationshipbetween the total length and body weight was found to be W =0.08998TL2"51. Thepresent investigation showed that the overfishing mortality (E>0.50) conditionsignificantly lowers the population of L. rohita in the Sylhet basin.